2011
DOI: 10.1152/jn.01083.2010
|View full text |Cite
|
Sign up to set email alerts
|

Multiple T-type Ca2+ current subtypes in electrophysiologically characterized hamster dorsal horn neurons: possible role in spinal sensory integration

Abstract: Whole cell patch-clamp recordings were used to investigate the contribution of transient, low-threshold calcium currents (I(T)) to firing properties of hamster spinal dorsal horn neurons. I(T) was widely, though not uniformly, expressed by cells in Rexed's laminae I-IV and correlated with the pattern of action potential discharge evoked under current-clamp conditions: I(T) in neurons responding to constant membrane depolarization with one or two action potentials was nearly threefold larger than I(T) in cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 66 publications
6
14
1
2
Order By: Relevance
“…The T-type current found in our dorsal horn neurons may have little contributions from Ca v 3.2, according to their pharmacology, and a reduced contribution of Cav 3.3, according to kinetic parameters [4]. The present results are in line with a previous report showing a higher expression of Cav 3.1 subunit in spinal cord neurons using a single-cell PCR [16]. Here, T-type currents are related to the presence of fast rebounds of high amplitude associated to highfrequency firing.…”
Section: Ionic Nature Of Rebound Responses In Deep Dorsal Horn Neuronssupporting
confidence: 92%
See 4 more Smart Citations
“…The T-type current found in our dorsal horn neurons may have little contributions from Ca v 3.2, according to their pharmacology, and a reduced contribution of Cav 3.3, according to kinetic parameters [4]. The present results are in line with a previous report showing a higher expression of Cav 3.1 subunit in spinal cord neurons using a single-cell PCR [16]. Here, T-type currents are related to the presence of fast rebounds of high amplitude associated to highfrequency firing.…”
Section: Ionic Nature Of Rebound Responses In Deep Dorsal Horn Neuronssupporting
confidence: 92%
“…We found that, applied at 100 μM, NiCl only reduced a ≈25 % of the current recorded. This observation is in line with a previous report showing a low efficacy of 200 μM NiCl and mibefradil at blocking I T recorded from dorsal horn neurons [16]. Increasing the concentration of NiCl to 1 mM produced a fast and reversible full block of the current, and application of the novel blocker TTA-P2 [6] also suppressed this current, supporting its identification as a T-type current.…”
Section: Ionic Nature Of Rebound Responses In Deep Dorsal Horn Neuronssupporting
confidence: 92%
See 3 more Smart Citations